Сервіс-орієнтований підхід при побудові інформаційної системи арт-менеджменту для управління закладами мистецтва у цифровому форматі - Калашнік, Д. О. (ХНУРЕ, 2025)
These theses examine the challenges in art management, address the problems of inflexible industry-wide management solutions, and provide effective ways to overcome these challenges. They also describe a general approach to creating flexible software that will allow you to manage collections, organize exhibІТions, create collections, contracts, loans, restoration tasks, client databases, and any other information in one intuІТive software.
Keywords: сервісний підхід; арт-менеджмент; мистецтво